Workshop Akselerasi Mutu Pembelajaran Melalui Differentiated Learning Pada Kurikulum Merdeka Belajar Di MAN 4 Jakarta - Rabiatul Adawiyah; Lukmanul Hakim; Kurniawan Kurniawan; Asep Abdurrohman; Febry Amirullah; Indriyani Idris (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
The current curriculum in Indonesia is the Independent Learning Curriculum (KMB). One of the recommended learning methods in KMB is differentiated learning (PB) because this learning accommodates differences, potentials, and needs of students in learning as per the KMB principle. Even so, most teachers have not implemented PB in learning, including at MAN 4 Jakarta. The Ministry of Education and Culture has actually released a book on PB as a guide for teachers, but most teachers lack the initiative to learn it autodidactically, especially older teachers. Therefore, community service was carried out in the form of a Differentiated Learning Workshop within the framework of the Independent Learning Curriculum to accelerate the quality of learning at MAN 4 Jakarta. This community service was carried out through three stages, namely pre-service which was carried out with preparation; service carried out with a workshop; and post-service which was carried out with monitoring and evaluation. The results showed that this community service was in the form of increasing teacher knowledge and skills in implementing differentiated learning.